Efektywność największych banków komercyjnych w Polsce - porównanie miar DEA z tradycyjnymi wskaźnikami efektywności - Kisielewska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In recent years traditional tools in assessing business performance such as various financial indicators have been completed by alternative measures derived from frontier efficiency methodologies. Among the latter Data Envelopment Analysis (DEA) is one of the most commonly used. This paper examines the relationship between DEA efficiency scores and traditional profitability ratios of the largest Polish banks over 9-year time period (1995-2003). Banks included in the study represent approximately 80% of the sector in terms of total assets. Results obtained in this research show a significant and positive relationship between DEA and profitability ratios in selected cases only, i.e. between Window DEA scores under first year formulation and 4 out of 5 traditional profitability ratios for data viewed in entire study horizon. In other cases correlation is either not significant or shows contradictory relations between obtained efficiency levels. This leads to conclusion that efficiency requires further studies hence different measures and approaches produce different results. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 156-179